The Babylonian Expedition of the University of Pennsylvania. Series A: Cuneiform texts - Clay, Albert Tobias; Hilprecht, H. V.; Myhrman, David Vilhelm; Poebel, Arno; Ranke, Hermann; Radau, Hugo; Langdon, Stephen (Dept. of Archaeology, University of Pennsylvania, 1893)
Vol. 1 pt. 1-2. Hilprecht, H.V. Old Babylonian Inscriptions chiefly from Nippur.- Vol. 3 pt. 1. Myrhman, D.V. Sumerian administrative documents.- Vol. 6 pt. 1. Ranke, Hermann. Babylonian legal and business documents. ...- Vol. 6 pt. 2. Poebel, Arno. Babylonian lagal and business documents. ...- Vol. 8 pt. 1. Clay, A.T. Legal and commercial transactions dated in the Assyrian, Neo-Babylonian and Persian periods.- Vol. 9. Hilprecht, H.V. Business documents of Murashû sons of Nppur dated in the reign of Artaxerxes I.- Vol. 10. Clay, A.T. Business documents of Murashû sons of Nippur dated in the reign of Darius II.- Vol. 14. Clay, A.T. Documents from the Temple archives of Nippur dated in the reigns of Cassite rulers.- Vol. 15. Clay, A.T. Documents from the Temple Archives of Nippur, dated in the reigns of Cassite rulers.- Vol. 17 pt. 1. Radau, Hugo. Letters to Cassite kings from the Temple archives of Nippur.- Vol. 20 pt. 1. Hilprecht, H.V. Mathematical, metrological and chronological tablets from the Temple library of Nippur.- Vol. 29 pt. 1. Radau, Hugo. Sumerian hymns and prayers to god Nin-Ib from the Temple library at Nippur.- Vol. 30 pt. 1 Radau, Hugo. Sumerian hymns and prayers to god Dumu-zi; or, Babylonian Lenten songs.- Vol. 31. Langdon, Stephen. Historical and religious textts from the Temple Library of Nippur. 1914.